Feasibility of high-resolution perfusion imaging using arterial spin labeling MRI at 3 Tesla - Kashyap, Sriranga; Oliveira, Ícaro Agenor Ferreira; Uludağ, Kâmil (Frontiers in Physiology, 2024)
Cerebral blood flow (CBF) is a critical physiological parameter of brain health and it can be non-invasively measured with arterial spin labelling (ASL) MRI. In this study, we evaluated and optimised whole-brain, high-resolution ASL as an alternative to the low-resolution ASL employed in the routine assessment of CBF in both healthy participants and patients. Two high-resolution protocols (i.e., pCASL and FAIR-Q2TIPS (PASL) with 2 mm isotropic voxels) were compared to a default clinical pCASL protocol (), all of whom had an acquistion time of ≈ 5 min. We assessed the impact of high-resolution acquisition on reducing partial voluming and improving sensitivity to the perfusion signal, and evaluated the effectiveness of z-deblurring on the ASL data. We compared the quality of whole-brain ASL acquired using three available head coils with differing number of receive channels (i.e., 20, 32 and 64 ch). We found using higher coil counts (32 and 64 ch coils as compared to 20 ch) offer improved SNR and improved acceleration capabilities that are beneficial for ASL imaging at 3T. The inherent reduction in partial voluming effects with higher resolution acquisitions improves the resolving power of perfusion without impacting sensitivity. In conclusion, our results suggest that high-resolution ASL (2 - 2.5 mm isotropic) has the potential to become a new standard for perfusion imaging at 3 T and increase its adoption into clinical research and cognitive neuroscience applications.